LACHblad. - Limburgs Actie Centrum Homofilie (LACH) (Hasselt : Limburgs Actiecentrum Homofilie, 1991)
Fonds Suzan Daniel (FSD)
Periodiciteit : tweemaandelijks
Redactie : Wijngaardstraat 1, 3500 Hasselt ; vanaf (1997) 37 : Lombaardstraat 20, 3500 Hasselt ; vanaf 09(1999-2000) 54 : Kuringersteenweg 179, 3500 Hasselt
Nederlands
Periodiek